MALAT1 in Liquid Biopsy: The Diagnostic and Prognostic Promise for Colorectal Cancer and Adenomas? - Cervena K; Siskova A; Jungwirth J; Volarić M; Kral J; Kohout P; Levy M; Vymetalkova V (International Journal of General Medicine, 2023)
Klara Cervena,1,2 Anna Siskova,1,2 Jiri Jungwirth,3,4 Marin Volarić,5 Jan Kral,6 Pavel Kohout,7 Miroslav Levy,8 Veronika Vymetalkova1,2,9 1Institute of Experimental Medicine, Czech Academy of Sciences, Prague, 142 00, Czech Republic; 2Institute of Biology and Medical Genetics, 1st Medical Faculty, Charles University, Prague, 128 00, Czech Republic; 3Institute of Physiology, 1st Faculty of Medicine Charles University, Prague, 121 08, Czech Republic; 4Department of Surgery, Weiden Clinic, Weiden in der Oberpfalz, 92637, Germany; 5Laboratory for Non-Coding DNA, Ruđer Bošković Institute, Zagreb, 10000, Croatia; 6Department of Hepatogastroenterology, Institute for Clinical and Experimental Medicine, Prague, 140 21, Czech Republic; 7Department of Internal Medicine, 3rd Faculty of Medicine Charles University and Faculty Thomayer Hospital Prague, Prague, 140 00, Czech Republic; 8Department of Surgery, First Faculty of Medicine, Charles University and Thomayer Hospital Prague, Prague, 140 59, Czech Republic; 9Biomedical Centre, Faculty of Medicine in Pilsen, Charles University in Prague, Pilsen, 323 00, Czech RepublicCorrespondence: Klara Cervena, Institute of Experimental Medicine, Czech Academy of Sciences, Videnska 1083, Prague, 142 00, Czech Republic, Email klara.cervena@iem.cas.czIntroduction: The development of colorectal cancer (CRC) is a multistep process accompanied by the accumulation of mutations that start from specific precancerous lesion – colorectal adenomas (CA). CRC incidence and mortality can be reduced by the early identification of these neoplasm. Colonoscopy is the most widely used screening method for CRC identification. Nowadays, clinical research interest is shifting to the use of liquid biopsy that may help with the early diagnosis of CA and CRC. In our previous study, we identified long non-coding RNA MALAT1 gene amplification associated with the development of CA.Methods: This study aimed to describe the potential of MALAT1 expression levels in the adenoma tissue of patients used in the previous study by real-time qPCR. Furthermore, we analysed the plasma samples of an independent group of patients with CA (n=97), CRC (n=101), and cancer-free individuals (CFI, n=48).Results: There was no difference in the MALAT1 expression level between CA patients with or without MALAT1 amplification. However, the plasma MALAT1 expression levels were significantly upregulated in patients with CRC and CA compared to CFI (for both p< 0.001). Moreover, a correlation between MALAT1 expression and histological types of adenomas was identified– high-CRC-risk adenomas also displayed the highest MALAT1 expression levels. Furthermore, in CRC patients, MALAT1 levels were associated with a response to therapy.Conclusion: MALAT1 expression levels could serve as a promising circulating biomarker for early CA and CRC diagnosis, and even as a predictor of therapy response in CRC patients.Keywords: MALAT1, colorectal adenomas, colorectal cancer, plasma, liquid biopsy